The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1515/jbcpp-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Seizure vulnerability and anxiety responses following chronic co-administration and acute withdrawal of caffeine and ethanol in a rat model

Abstract: These findings suggest that the chronic co-administration of caffeine and ethanol and the acute withdrawal from these drugs lead to anxiogenic effects and increased seizure vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In juvenile rats, caffeine combined with ethanol increased the vulnerability to seizures triggered with PTZ, whereas caffeine alone had a protective effect [49].…”
Section: Protective Effects Of Caffeinementioning
confidence: 98%
“…In juvenile rats, caffeine combined with ethanol increased the vulnerability to seizures triggered with PTZ, whereas caffeine alone had a protective effect [49].…”
Section: Protective Effects Of Caffeinementioning
confidence: 98%
“…In accordance with this possibility, chronic caffeine was shown to increase anxiogenic-like effects associated with nicotine and alcohol withdrawal in rodents. 14,80 Here, we failed to identify alterations in the expression of hippocampal 5-HT 1A , which suggests that this receptor, in the hippocampus, does not play a critical role in the anxiety-like behavior evoked by lifetime caffeine. Arnold and colleagues 71 showed that caffeine exposure during adolescence does not affect mRNA expression of htr1a, the serotonin 1a receptor gene, however, it downregulates mRNA expression of other proteins involved in serotonergic transmission in the dorsal raphe nucleus of rats.…”
Section: Discussionmentioning
confidence: 81%
“…Initially, the Elevated Plus-Maze (EPM) was used to assess anxiety in rats (Matovu D et al, 2018). EPM is made up of two open arms (50 10 cm) with a 5cm-high edge and two closed arms (50 10 cm) with 40-cm-high walls that extend from a shared center platform (5 5 cm).…”
Section: Elevated Plus-mazementioning
confidence: 99%